THE INFLUENCE OF ASSET MANAGEMENT ON OPTIMIZING THE UTILIZATION OF FIXED ASSETS IN THE PALEMBANG CITY GOVERNMENT - Miftahul Jannah; Rita Martini; Rosy Armaini (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The main objective of this study is to explore and evaluate the impact of asset inventory, assessment, supervision, and control on enhancing the efficiency of fixed asset utilization in the administrative setup of Palembang city. The research was conducted within the premises of Palembang City Government with the involvement of a total of 40 individuals. The selection of participants was based on their relevance to the study objectives and the data obtained from them was analyzed using SEM PLS Structural Equation Modeling technique. The analysis was carried out through the utilization of the SmartPLS 4.0 software application. The outcomes of the investigation suggest that effective management practices related to asset inventory, assessment, supervision, and control can lead to significant enhancements in the effective utilization of fixed assets within the administrative framework of Palembang.